Seni Hias Tempel Keramik Kesultanan Cirebon: Toleransi dalam Kebinekaan - Naniek Harkantiningsih (Balai Arkeologi Maluku, 2017)
The Sultanate of Cirebon is the center of the Islamic empire that grew from the 15th century, in fact not only grew in the religious, bureaucratic, and commercial sphere, but also established cooperation with the Dutch, especially in the early 18th century, even become to region of the territory of VOC until the Dutch East Indies government. One of the proofs of the relationship, is the form of ceramic tiles from the Netherlands which until now used as decoration wall of the palace, mosque, and tombs. The pattern of ceramic tiles is biblical story. The existence of ceramic tiles of the biblical story in Cirebon as an area of the Islamic empire that was very influential at that time, certainly be uniqueness. Therefore, the purpose of this papers is to know the reasons for the preservation of the ornamental art of ceramic outboard bible stories in the center of government and sacred buildings characterized by Islam. The method used is qualitative analysis, context analysis, and literature study. The preservation of this ornamental art may also be linked to the tolerance of diversity, which is the current government policy program. The use of ceramic outboard art of Biblical story, both in profane and sacred building makes one of the typical culture of Cirebon, because the people of Cirebon and the Sultanate relatives still maintain the unity and preserve the cultural heritage.Kesultanan Cirebon sebagai pusat kerajaan Islam yang berkembang dari abad ke-15an, pada kenyataannya tidak hanya tumbuh dalam lingkup keagamaan, birokrasi, dan perniagaan, tetapi juga menjalin kerjasama dengan Belanda. Terutama pada awal abad ke-18an, bahkan menjadi wilayah kekuasaan VOC hingga pemerintahan Hindia Belanda. Salah satu bukti hubungan itu, berupa tegel keramik asal Belanda yang hingga kini dipakai sebagai hiasan tembok keraton, masjid, dan makam. Tegel keramik tersebut bermotifkan cerita Alkitab. Keberadaan tegel keramik cerita Alkitab di Cirebon sebagai wilayah kerajaan Islam yang sangat berpengaruh pada masa itu, tentu menjadi keunikan. Tujuan penulisan ini yaitu, mengetahui alasan pelestarian seni hias tempel keramik cerita Alkitab di pusat pemerintahan dan bangunan sakral bercirikan Islam. Metode yang digunakan ialah analisis kualitatif, analisis konteks, dan studi kepustakaan. Pelestarian seni hias ini mungkin dapat pula dihubungkan dengan toleransi kebinekaan, yang menjadi program kebijakan pemerintah saat ini. Penggunaan seni hias tempel keramik cerita Alkitab, baik di bangunan profan maupun sakral menjadikan salah satu budaya khas Cirebon, karena masyarakat Cirebon dan kerabat Kesultanan masih menjaga keutuhan dan melestarikan tinggalan budaya tersebut.